P100 Research priorities to reduce the impact of musculoskeletal disorders. (23rd April 2022) - Paskins, Zoe; Farmer, Clare E; Jones, Richard K; Clark, Amanda; Troeberg, Linda; Pandit, Hemant; Richardson, Stephen M; Loughlin, John; Brown, Christopher A; Taylor, Elizabeth J; Le Maitre, Christine L; Wilcox, Ruth K; et al.
Abstract: Background/Aims: Involving research users in setting priorities for research is essential to ensure research outcomes are patient-centred and to maximise research value and impact. In 2019, Versus Arthritis convened a Musculoskeletal Disorders (MSKD) Research Advisory Group (RAG) which included 25 members: people with musculoskeletal conditions, researchers and healthcare professionals. The RAG identified a need for a research prioritisation exercise for adult non-inflammatory MSKD. Methods: The Child Health and Nutrition Research Initiative (CHNRI) method was selected. The MSKD RAG identified, through consensus, four research Domains: Mechanisms of Disease; Diagnosis and Impact; Living Well with MSK disorders and Successful Translation. Following ethical approval, an initial electronic survey was distributed to stakeholders (people with musculoskeletal conditions, researchers, healthcare professionals, industry, research funders, healthcare providers, government and charities) asking for important research uncertainties in the four domains. Uncertainties were organised into themes and refined into research questions using a series of MSKD RAG workshops. Research questions underwent lay review to optimise readability. A second e-survey was distributed to stakeholders as above, where participants were asked to score each research question for two criteria, importance and impact, on a 1-10 numeric rating scale. Median criterion scores for impact and importance were calculated for each question and summed to create a total score. Research questions were ranked according to total score. Results: The first survey had 209 respondents, who described 1290 research uncertainties, which were refined into 68 research questions. 285 people responded to the second survey, of which 189 fully completed. 74(39.2%) were public/lay responders, 48(25.4%) researchers, 43(22.8%) clinicians, 24(12.6%) other/unrecorded. The research questions, total scores and rankings are summarised in Table 1 . Total scores ranged from 12 to 18 (maximum possible score 20). Conclusion: For the first time, we have summarised priorities for research across MSKD, from discovery science to applied clinical and health research, including translation. Key priorities include developing and testing new treatments, better targeting of treatments, early diagnosis, prevention and better understanding and management of pain, with an emphasis on understanding the underpinning mechanisms. We present a call to action to researchers and funders to target these priorities. Disclosure: Z. Paskins: Grants/research support; NIHR, Versus Arthritis, Royal Osteoporosis Society. C.E. Farmer: None. R.K. Jones: None. A. Clark: None. L. Troeberg: Grants/research support; Versus Arthritis. H. Pandit: Consultancies; Depuy J&J, Zimmer Biomet, Smith and Nephew, Medacta International, Meril Life, JRI Orthopaedics, Invibio and Kennedy's Law. Grants/research support; NIHR, VA (Versus Arthritis) and UKIERI (UK India Education and Research Initiative). S.M. Richardson: None. J. Loughlin: None. C.A. Brown: Grants/research support; Versus Arthrtitis. E.J. Taylor: None. C.L. Le Maitre: None. R.K. Wilcox: Grants/research support; EPSRC, Versus Arthritis, NIHR, DePuy Synthes. F.L. Bishop: None. E. Salt: None. E.M. Clark: Grants/research support; Versus Arthritis, NIHR. Other; I am Associate Editor of Journal of Bone and Mineral Research Plus for which I receive a salary, I am part of the Lot 2 provider for analysis of the national Joint Registry of England and Wales, funded by HQIP. D.A. Andersson: None. M. McCarron: None. D.J. Mason: None. C.M. Wilkinson: None. T. Barlow: None. G.M. Peat: None. F.E. Watt: Consultancies; Pfizer.